Validity and reliability of the my jump® 2 app to measure vertical jump performance in beach volleyball players - Pereira de Souza, L. A.; Freitas Nunes, J. T.; Ghedini Gheller, R.; Martins de Souza, G. P.; Libardoni dos Santos, J. O.; de Souza Bezerra, E. (Apunts Sports Medicine, 2025)
Background/Objective This study aimed to assess the validity and reliability of the My Jump® 2 app for measuring vertical jump height on sand. We hypothesized that the app would demonstrate good reliability (ICC > 0.75) and acceptable agreement (bias < 2 cm, CCC = 0.95) with 2D video analysis.